2010
DOI: 10.1093/jat/34.2.89
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Triazolam and  -Hydroxytriazolam in Guinea Pig Hair After a Single Dose

Abstract: A sensitive liquid chromatography-tandem mass spectrometry method is presented for determination of triazolam and alpha-hydroxytriazolam in guinea pig hair after a single dose of triazolam. Eighteen guinea pigs were divided into three dosage groups (10, 100, and 500 microg/kg) and administrated a single dose of triazolam intragastrically. Before administration, drug-free hair was shaved from their back. Newly grown hair in shaved area was collected every seven days after administration. About 20 mg of decontam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The level detected in this particular hair case indicated low intake of triazolam when compared to other similar publications [8,9] although these cases involved administration of triazolam to pigs or prescribed sedative (triazolam) with unknown use/compliance. It is possible that the dark hair of this case improved the detection possibilities since the high melanin content improves absorption of basic drugs such as triazolam.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…The level detected in this particular hair case indicated low intake of triazolam when compared to other similar publications [8,9] although these cases involved administration of triazolam to pigs or prescribed sedative (triazolam) with unknown use/compliance. It is possible that the dark hair of this case improved the detection possibilities since the high melanin content improves absorption of basic drugs such as triazolam.…”
Section: Discussionmentioning
confidence: 50%
“…The metabolite was not detected in the hair, a finding which could be attributed to the higher LOQ of this more polar compound and lower degree of incorporation of the metabolite into hair. Sun et al [8] found higher concentrations of the metabolite in guinea pig hair than the main drug triazolam. However, their data interpretation was also inhibited by the same less sensitive analysis of the metabolite than the parent drug (five times less), and their observation cannot be used as a general guideline since the study was performed on pigs and only involved four observations.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Since the pH in melanocytes is lower than that in plasma, lipophilic and basic drugs enter pigmented hair more than hydrophilic or acidic drugs [2]. The incorporation of selected benzodiazepines into hair has been studied using rat or human hair [3][4][5][6][7]. However, the interpretation of the quantitative results in hair from benzodiazepine, especially diazepam, users is not straightforward because diazepam is metabolized to temazepam and nordiazepam, both of which are further metabolized to oxazepam.…”
Section: Introductionmentioning
confidence: 99%